Isolation and characterization of novel acetogenic strains of the genera Terrisporobacter and Acetoanaerobium - Böer, Tim; Schüler, Miriam Antonia; Lüschen, Alina; Eysell, Lena; Dröge, Jannina; Heinemann, Melanie; Engelhardt, Lisa; Basen, Mirko; Daniel, Rolf; Poehlein, Anja (Frontiers in Microbiology, 2024)
Due to their metabolic versatility in substrate utilization, acetogenic bacteria represent industrially significant production platforms for biotechnological applications such as syngas fermentation, microbial electrosynthesis or transformation of one-carbon substrates. However, acetogenic strains from the genera Terrisporobacter and Acetoanaerobium remained poorly investigated for biotechnological applications. We report the isolation and characterization of four acetogenic Terrisporobacter strains and one Acetoanaerobium strain. All Terrisporobacter isolates showed a characteristic growth pattern under a H2 + CO2 atmosphere. An initial heterotrophic growth phase was followed by a stationary growth phase, where continuous acetate production was indicative of H2dependent acetogenesis. One of the novel Terrisporobacter isolates obtained from compost (strain COM T ) additionally produced ethanol besides acetate in the stationary growth phase in H2supplemented cultures. Genomic and physiological characterizations showed that strain COM T represented a novel Terrisporobacter species and the name Terrisporobacter vanillatitrophus is proposed (=DSM 116160 T =CCOS 2104 T ). Phylogenomic analysis of the novel isolates and reference strains implied the reclassification of the T. petrolearius/T. hibernicus phylogenomic cluster to the species T. petrolearius and of the A. noterae/A. sticklandii phylogenomic cluster to the species A. sticklandii. Furthermore, we provide first insights into active prophages of acetogens from the genera Terrisporobacter and Acetoanaerobium. * data from [19] **data from [20,22] ***data from [22]